Fusarium species from Malaysian soils - Lim, W. H.; Varghese, G. (Malaysian Society of Applied Biology, 1977)
A qualitative and quantitative assessment of the population of Fusarium spp. in soil under cultivated and non-cultivated habitats was carried out, Within a total of 30 locations sampled in Peninsular Malaysia, F. solani and F. oxysporum were the most widespread species. F. solani predominated over F. oxysporum. Next in abundance were F. roseum and F. moniliforme. Fusarium epispbaeria, F.lateritium and F. tricinctum were occasionally isolated. Five cultivars of F. roseum viz 'Longipes, 'Acuminatum' 'Equiseti', 'Sernitectum', and 'Sambucinum' and two cultivars of F. moniliforme were also distinguished. Thus out of the nine species recognised by Snyder and Hansen seven were recorded in Malaysian soils. Primary jungle had none to low populations of soil fusaria while secondary jungle and cultivated habitats had low to abundant populations. Compared to secondary jungle, cultivated soils had more clonal types of F. solani and F. oxysporum. Between long-term crops and short-term crops, the former had generally higher Fusarium populations. Descriptions of the seven species isolated are given as an aid to identification of local Fusarium species